Advances in hepatoprotective medicinal plants research (Bangladesh Journal of Pharmacology, 2017)
Hepatic dysfunction is a major catastrophe that challenges the health concern researchers. Multiple factors such as biological, chemical and drug overdose are associated with liver disorders. Man-made pharmaceutical preparations, which are usually used for the treatment, further accelerate the toxification of the liver. In this situation, a great reliance has been evident on natural products which seem promising in dealing with liver diseases effectively. Plants are the basis of innate products, or dynamic constituents named as phytochemicals, which have been analyzed for their hepatoprotective potential and a review article on hepatoprotective plants was published in 2014 in Bangladesh Journal of Pharmacology. After that, a number of researches have been completed to identify new hepatoprotective medicinal plants. The purpose of this review was to update the information until now.